(untitled) (Research, Society and Development, 2021)
Worker’s health is an essential theme, especially when understanding that work builds the person. In the area of ​​health, there is an even clearer need for care for these people. This article aims to tell the experience lived as a multidisciplinary resident in mental health, developing actions thinking about the mental health of health workers in a management context and in primary care. It is an experience report that uses as methodological tools the field diary and participant observation, constituting a qualitative research that uses content analysis. The proposed interventions, although punctual, had positive impacts, demonstrating the importance of affection and pause for these workers, fostering collective support. Thus, residency is perceived as a possibility of care combined with continuing education in health, as it is capable of pointing out existing gaps and doing something about the care demands made.